Impact of Digital Transformation on The Innovation Capacity of Chinese-Listed Firms: Role of Government Subsidies - Zhu Yiming; Leo Delaric Manansala (International Journal of Applied Business and International Management, 2024)
As digital transformation progresses, listed Chinese firms are undergoing significant changes in their practices. These changes are crucial for establishing and maintaining a competitive advantage. This research investigates the process by which digital transformation affects firms' capacity to innovate, specifically focusing on the influence of government subsidies. The data was obtained from 1,063 publicly traded in China from 2018 to 2022 with a total of 4,027 data points. A fixed-effects model, stepwise regression analysis, and bootstrapping techniques were employed to construct the models. To address the conventional quantitative constraints and provide a nuanced comprehension of digital transformation's influence, this study uses textual analysis. Research has shown that digital transformation has a substantial positive impact on the ability of companies to innovate. Additionally, government subsidies are proven to have a role in facilitating this process. This paper offers a fresh viewpoint on comprehending the mechanism of government subsidies for digital transformation and corporate innovation capability. It also provides evidence supporting the idea that government subsidies may enhance innovation incentives more effectively.